Variables as a Substantial Element of the Scientific Method - Arroyo Valenciano, Juan Antonio (2021)
The scientific community acknowledges that both the problem and hypothesis not only comprise two relevant phases of the scientific method, but also share a common, more substantial element that conforms its very essence - variables. The success and precision required in order to obtain valid knowledge and reliable conclusions in the field of education depends on the rigor used to define such variables. A document-based theoretical study of sources in the field of education adhering to this research methodology and  published between 2000 and 2020 was conducted in order to determine if the conditions of the scientific method were met. This study acknowledge that such variables are an intrinsic part of the structure of both the problem and hypothesis. Variables serve as references and are an essential part of the operative statement without contemplating norms or considerations that the researchers must adhere to when establishing such definitions. This study, therefore, presents a three-dimensional conceptual model, that empowers  researchers to delimit essential operative and instrumental meanings of variables as a substantial element of the scientific method.